Long-term gynecological complications after conservative treatment of placenta accreta spectrum - Herzberg, Shmuel; Ezra, Yossef; Haj Yahya, Rani; Weiniger, Carolyn F.; Hochler, Hila; Kabiri, Doron (Frontiers in Medicine, 2022)
Objective: to examine the association between conservative treatment for PAS (placenta accreta spectrum) and subsequent gynecological and fertility complications. Methods: All women who underwent conservative treatment for PAS between January 1990 and December 2000 were included in this retrospective cohort study conducted in a tertiary teaching hospital. Gynecological and fertility complications experienced after the index delivery were collected from the medical records and telephone questionnaires. This data was compared to an age and parity-matched control group of women without PAS. Results: The study group included 134 women with PAS managed conservatively and 134 controls with normal deliveries matched by parity and age. Women in the PAS group required significantly more postpartum operative procedures such as hysteroscopy or D&C (OR=6.6; 95%CI: 3.36-13.28; P-value=<0.001). Following the index delivery, there were 345 pregnancies among 107 women who attempted conception following conservative treatment for PAS versus 339 pregnancies among 105 women who attempted conception in the control group. Among women who attempted conception following conservative treatment for PAS 99 (92.5%) delivered live newborns (a total of 280 deliveries) versus 94 (89.5%) in the control group, (a total of 270 live newborns, p=0.21). The need for fertility treatments was not different between the two groups (OR=1.22; 95%CI: 0.51-2.93; P-value=0.66). Conclusions: After conservative treatment for PAS, significantly more women required complementary procedures due to retained placenta and/or heavy vaginal bleeding. There was no evidence of fertility impairment in women post-conservative treatment for PAS.